ROMANIA’S LABOUR FORCE IN REGIONAL PROFILE AFTER THE ACCESSION TO THE EUROPEAN UNION - Mihai Alexandru CHIȚEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper approaches the issue of the labour force from Romania in regional profile at a decade after the accession to the European Union. The economic, political, technological and financial changes occurred at different aggregation levels have, profoundly, influenced the volume and structure of the labour force at national level. The analysis is based on statistical data available at national and European level and follows the evolution in regional profile. The result reveal an unprecedented dynamic of the national labour force and support the need for efficient public policies in the field of education and employment, adapted to the new coordinates of the economic activity.